Shedding a New Light on Skin Aging, Iron- and Redox-Homeostasis and Emerging Natural Antioxidants - Charareh Pourzand; Andrea Albieri-Borges; Nico N. Raczek (MDPI AG, 2022)
Reactive oxygen species (ROS) are necessary for normal cell signaling and the antimicrobial defense of the skin. However excess production of ROS can disrupt the cellular redox balance and overwhelm the cellular antioxidant (AO) capacity, leading to oxidative stress. In the skin, oxidative stress plays a key role in driving both extrinsic and intrinsic aging. Sunlight exposure has also been a major contributor to extrinsic photoaging of the skin as its oxidising components disrupt both redox- and iron-homeostasis, promoting oxidative damage to skin cells and tissue constituents. Upon oxidative insults, the interplay between excess accumulation of ROS and redox-active labile iron (LI) and its detrimental consequences to the skin are often overlooked. In this review we have revisited the oxidative mechanisms underlying skin damage and aging by focussing on the concerted action of ROS and redox-active LI in the initiation and progression of intrinsic and extrinsic skin aging processes. Based on these, we propose to redefine the selection criteria for skin antiaging and photoprotective ingredients to include natural antioxidants (AOs) exhibiting robust redox-balancing and/or iron-chelating properties. This would promote the concept of natural-based or bio-inspired bifunctional anti-aging and photoprotective ingredients for skincare and sunscreen formulations with both AO and iron-chelating properties.